Small Size Wideband Monopole Antenna with Five Notch Bands for Different Wireless Applications - Bala, Susmita; Reddy, P. Soni; Sarkar, Sushanta; Sarkar, Partha Pratim (Společnost pro radioelektronické inženýrství, 2022)
A broadband planar monopole antenna with five notch bands is proposed here. The antenna provides broadband from 1.94 GHz to 15.4 GHz with five notch bands covering 3.1-4.1 GHz, 6-6.4 GHz, 8.2-9.2 GHz, 10-11.6 GHz, and 12.38-12.89 GHz. These notch bands are effectively used to remove undesired interferences from the WiMAX (3.2-3.8 GHz), partial standard C band (5.850-6.415 GHz), partial ITU band (8.025-8.4 GHz), partial X band (8-12 GHz), and partial Ku downlink frequency band (12.2-12.7 GHz). The notch bands have been realized by etching three notch elements on the patch, feed line, and two small narrow open-ended slots on the ground plane. The design of the proposed antenna is very simple and it utilizes only the volume of 20×40×1.6 mm3. The antenna is useful for wideband fast data communication systems.
Keywords: Wideband; monopole; notch band; S11 parameter; gain; radiation pattern